Capillary Refill Technology to Enhance the Accuracy of Peripheral Perfusion Evaluation in Sepsis. (September 2022) - Gillespie, Jordan; Hansen, Matthew; Samatham, Ravi; Baker, Steven D.; Filer, Scott; Sheridan, David C.
Background: Monitoring of capillary refill time (CRT) is a common bedside assessment used to ascertain peripheral perfusion in a patient for a vast array of conditions. The literature has shown that a change in CRT can be used to recognize life-threatening conditions that cause decreased perfusion, such as sepsis, and aid in resuscitation. The current practice for calculating CRT invites subjectivity and produces a highly variable result. Innovative technology may be able to standardize this process and provide a reliable and accurate value for use in diagnostics and treatment. This study aimed to assess a new technology (DCR by ProMedix Inc.) for rapid, bedside, and noninvasive detection of CRT.Methods: This was a secondary analysis of a prospective observational study evaluating the accuracy of new technology towards CRT-guided diagnosis of sepsis. It was carried out in the adult emergency departments (ED) of an academic tertiary care medical center. Patients seeking care in the ED were determined eligible if they were > 18 years in age and exhibited chief complaints suggestive of possible sepsis. The CRT produced by the technology was compared to the gold standard manual waveform assessment.Results: 218 consecutive subject enrollments were included and multiple measurements were made on each patient. Data with irregular waveforms were excluded. A total of 692 waveforms were evaluated for CRT values by a pair of trained PhD biomedical engineers. The average age of the cohort was 50.62 and 51.4% female. Results showed a Pearson correlation coefficient of 0.91 for the device CRT compared to the CRT gold standard. The Pearson correlation coefficient for the two independent engineering review of the waveform data was 0.98. This device produces accurate, consistent results and eliminates the subjectivity of CRT measurements that is in practice currently.